Demographic Changes and Their Implications in a Nonacademic Emergency Department in Switzerland: An 11-Year Trend Analysis (2000–2010) of 104, 510 Patients. (14th June 2012) - Businger, Adrian P.; Kaderli, Reto; Burghardt, Larissa R.; Osinga, Rik; Liesch, Martin; Furrer, Markus
Abstract : Background . Recent demographic developments outline a worldwide increase in the older population. The aim of the present study was to assess whether the sociodemographic characteristics of patients with emergency department (ED) admissions have changed over time. Methods . This study utilized the database of a level I accident and emergency unit in eastern Switzerland, a prospective database of consecutive patients aged ≥16 admitted between 2000 and 2010. Sociodemographic data were extracted as well as date and time of admission, instances of referral, diagnosis, time needed for ED treatment, and nursing effort. Results . Data from 104, 510 patients were utilized. There was a significant increase in the percentage of patients aged ≥65 years (from 25.7 per cent (1, 775/6, 905) to 29.6 per cent (3, 845/12, 340); P trend < 0.01 ). The mean length of stay in the ED was significantly longer (from 140.3 minutes, SD 91.9 to 169.5 minutes, SD 101.1; P trend < 0.01 ) and the percentage of illness as the cause of admission was significantly higher over time (from 58.3 per cent to 59.4 per cent; P trend < 0.01 ). Conclusions . The change in patients' demographics found and the resulting considerably increasing workload in EDs might be helpful for planning purposes, future training of ED personnel, and allocating resources.